Political competition and tax revenues in developing countries - Urbain Thierry Yogo; Martine M. Ngo Njib (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Building on the literature of the political economy of taxation, this article explores the relationship between political competition and tax revenues using a sample of 89 developing countries from 1988 to 2010. Owing to the inertia of tax variables, we estimate a dynamic panel data model using the Blundell and Bond two-step System-GMM. The analysis led to the following results: political competition positively and significantly affects total tax revenues; however, this general pattern differs slightly across the type of taxes; and the net effect of political competition on tax revenues is negative for countries which have adopted fiscal rules.
Keywords: C72; D72; H21; 330; level of tax revenues; political competition; volatility of tax revenues